Teacher-Implemented Response Interruption and Redirection: Training, Evaluation, and Descriptive Analysis of Treatment Integrity. Issue 1 (January 2018) - Giles, Aimee; Swain, Shelley; Quinn, Louise; Weifenbach, Brittany
Response interruption and redirection (RIRD) is an effective intervention for decreasing stereotypy. During RIRD, contingent on occurrences of stereotypy, therapists interrupt the behavior and prompt the participant to complete an alternative response. Although RIRD has been implemented by teachers in classrooms, it requires continuous monitoring of participants to be implemented with fidelity and may be difficult for teachers to manage. The present study evaluated the effectiveness of RIRD when implemented in classrooms. In addition, we evaluated if novice teaching assistants could be trained to implement RIRD. Finally, a descriptive analysis of treatment integrity errors during RIRD was conducted. Three children and teaching assistants participated. Following a written instructions baseline, the teaching assistants were trained to implement RIRD using modeling, rehearsal, and feedback. The training increased the accuracy of RIRD implementation for all participants. Incorrectly initiating and terminating RIRD were the most common treatment integrity errors observed.